DAMPAK PERSEPSI BUDAYA terhadap Kesehatan Reproduksi Ibu dan Anak di Indonesia - Khasanah, Nur (IAIN Pekalongan, 2011)
Reproduction for women is sunnatullah, the health of a mother in childbirth is a necessity so that the child will be born healthy too, but sometimes women are stuck in the myths, traditions and cultural perceptions that occur in the presence of certain taboos will eat healthy foods so that the will result in death, then this is where the need for cultural deconstruction of discourse that is built up so it can be enlightened and enlightening for mothers and children born